Using rice bran as a patisserie ingredient in project-based learning in the food engineering study program at UNY - Rizqie Auliana; Abdul Rasid Bin Abdul Razzaq (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
The number of people with non-communicable diseases (NCD) and degenerative diseases tends to increase from time to time. The diseases are the results of a bad diet and free radicals. Rice bran is one of the food sources containing high fiber and antioxidants. However, it is rarely used as a food product. Rice bran may become the ingredient of patisserie products for NCD diet. These rice bran-based patisseries are made in the Food Engineering Education study program of the Faculty of Engineering at UNY. Through Project-based Learning (PjBL), the fourth-semester students taking the Bakery Processing course learned how to make rice bran products. There were 30 students participating in this research which was conducted from June to September 2018. Based on the result of this study, it was found that the average of students’ knowledge pre-test score was 20.90, and the posttest average score was 23.10. In terms of students’ attitudes, the average pre-test score was 46.25, and the average post-test score was 49.80. The students’ skills at making rice bran-based patisseries are considered “Good” because the score ranges between 93 and 100. PjBL is considered effective to be implemented in the Food Engineering class because it can improve students’ knowledge, attitude, and skill scores.